Bibliometric analysis of research trends in stem cell therapy for knee osteoarthritis over the period 2001–2021 - Chen, Runzhi; Jiang, Yanyan; Lu, Laiya; Wang, Pei; Huang, Dongya; Wang, Jingyi; Liu, Zheng; Qin, Shaojie; Yin, Feng (Frontiers in Cell and Developmental Biology, 2022)
Stem cells therapy has been regarded as a promising treatment to Knee Osteoarthritis, but few bibliometric studies have been performed. Bibliometric analysis is helpful to identifying the most influential studies in a specific field and can evaluate the global research trends in stem cells therapy for Knee Osteoarthritis. The Web of Science Core Collection was searched on for publications posted from 2001 to 2021. Publication performance was analyzed using several bibliometric parameters, including VOSviewer to identify the research landscape of trendy topics, and CiteSpace to show keywords with the strongest citation bursts. From 2001 to 2020, in total, 1345 publications explored the research on stem cells in Knee Osteoarthritis. The United States contributed the largest number of publications and topped the list of international collaboration. As for the overall number of articles and citations, Tokyo Medical and Dental University ranked first. The Journal of OSTEOARTHRITIS AND CARTILAGE had the largest number of publications. Ichiro, Sekiya who published 32 articles, was the first cited author. Keywords with the most frequent occurrence were “osteoarthritis”, “mesenchymal stem cells” and “cartilage” by the descending order. “fibroblast growth factor” and “extracellular vesicle” became the first and last searched theme terms respectively. The number of publications and citations in stem cells for Knee Osteoarthritis stays growing. The mechanism of cartilage repair and paracrine may keep being the research hotspots. Stem cells therapy has been gradually advanced from basic research into clinical application stages.